(R‐X‐R)4‐Motif Peptides Containing Conformationally Constrained Cyclohexane‐Derived Spacers: Effect on Cellular Uptake. (13th October 2017) - Bhosle, Govind S.; Fernandes, Moneesha
Abstract: Arginine‐rich peptides having the (R‐X‐R) n motif are among the most effective cell‐penetrating peptides (CPPs). Herein we report a several‐fold increase in the efficacy of such CPPs if the linear flexible spacer (‐X‐) in the (R‐X‐R) motif is replaced by constrained cyclic 1, 4‐substituted‐cyclohexane‐derived spacers. Internalization of these oligomers in mammalian cell lines was found to be an energy‐dependent process. Incorporation of these constrained, non‐proteinogenic amino acid spacers in the CPPs is shown to enhance their proteolytic stability. Abstract : The "X" factor : An optimum balance between constraint and flexibility in the 1, 4‐substituted‐cyclohexane‐derived spacer "X" in arginine‐rich (R‐X‐R)‐motif peptides leads to enhanced cell‐penetration properties. These peptides are also resistant to proteolytic degradation.